Chemical characteristics of an Oxisol after urea and potassium chloride fertilization in a protected environment (Scientia Agricola, 2001)
The production of healthy, high quality vegetables and the development of technologies for continuous supply to the market are important factors determining the adaption of protected cultivation systems by an increasing number of growers. Due to the little knowledge on soil management practices under these conditions, high fertilizer rates are normally applied, causing salinity problems and nutricional unbalances. The objective of this paper was to evaluate the effects of urea and potassium chloride applications on the chemical characteristics of an Eutrorthox, mainly on its acidity and potassium saturation. The N was applied in rates of 13.3 and 39.9g m-2 and the K in rates 5.5 and 16.6 g m-2, in a fatorial (2X2+1) design, including a control. Pepper plants (Capsicum annuum, Mayata cultivar) were grown under protected condition, during 34 weeks. After seedling rooting, the nutrients were applied at the rate of one sixth of the total at ten day intervals, up to 60 days. It was observed that urea did not acidify the soil probabily due to its high buffering capacity. The nitric and ammoniacal forms of N were directly effeted by the N rates applied in relation to the soil. In the treatment with N, the roots showed better development compared to the control. However, the highest K rate, applied as KCl, decreased root growth, probably due to the high soil K concentration and possible salinity effects, resulting in more than 5.0 mmol c dm-3 of K and more than 5.3% of K saturation in the exchange complex.